Literacies in early childhood : foundations for equity and quality - Woods, Annette; Exley, Beryl (Docklands, Victoria : Oxford University Press, 2020)
"A collection of expert voices on the theoretical frameworks and approaches for teaching literacy in the early childhood years. Literacies in early childhood: foundations for equity and quality is a rigorous and engaging foundational text that offers access to a broad range of voices and perspectives on quality literacy learning and teaching, and on how equity and literacy come together in education. It takes a deliberately balanced approach to literacy learning in early childhood education, and values the child as a learner and respects the teacher as a professional." -- provided by publisher.
Part 1. Understandings of literacy -- Part 2. Transitions, quality and equity -- Part 3. Practical considerations and theoretical conundrums -- Part 4. The intellectual and political work of literacy teaching.
"Literacies in Early Childhood: Foundations for Equity and Quality is a rigorous and engaging foundational text that offers access to a broad range of voices and perspectives on quality literacy learning and teaching, and on how equity and literacy come together in education. It takes a deliberately balanced approach to literacy learning in early childhood education, and values the child as a learner and respects the teacher as a professional. Structured across four parts, it aims to open discussion and encourage quality and equity in literacy education across schools and early childhood education contexts. Part 1, Understandings of Literacy, provides a foundation for thinking about definitions of literacies. Part 2, Transitions, Quality and Equity, offers a range of theoretical tools and practical examples of how teachers, educators and diverse groups of students can work together. Part 3, Practical Considerations and Theoretical Conundrums, focuses on the engagement of young children in literacy learning, offering case studies and examples from contemporary research and practice. The final part, The Intellectual and Political Work of Literacy Teaching, analyses what it means to be a literacy teacher in today's contexts." -- Back cover.
Includes bibliographical references and index.
Keywords: Literacy -- Study and teaching (Early childhood); Literacy -- Study and teaching (Elementary)